Russian Labour Market: Adaptation without Restructuring - Ростислав Исаакович Капелюшников (Journal of Economic Sociology, 2010)
This is the first time when an integral «portrait» of the Russian labour market in transition is given in the Russian economic literature. The first part covers the differences in the dynamics of the employment, unemployment, working time and wage indicators in Russia and the countries of Central and Eastern Europe. The specific focus is given to the various non-standard forms of adaptation on the Russian labour market, – part-time and additional employment, wage arrears, informal payment and etc. The second part is devoted to the analysis of the employment strategies of the Russian industrial enterprises. The dominating topic in the paper is the predominance of the informal rules and norms, which facilitate the short-term adaptation to the ongoing changes and slow down the long-term restructurisation of the Russian labour market.